Analisis Daycare sebagai Alternatif Pengasuhan Anak dalam Prespektif Islam di Era Digital - Rochmatul Muna (Pascasarjana IAI Al-Khairat Pamekasan, 2025)
Changing times and the dynamics of modern life make parents play a dual role as productive workers and caregivers for their children. They are faced with a dilemma regarding the upbringing of their children. The role and influence of daycare as a childcare option is a very important thing to consider. The aim of the research is to provide a more comprehensive understanding of the process of caring for and developing children in daycare, the advantages and disadvantages of daycare for parents and children, and the impact of daycare on parents and children. The type of method that researchers use in this case is a qualitative method. The type of approach used is a qualitative descriptive approach. The informants in this research included daycare managers, parents or guardians of students, and children who were involved in the daycare program. Data collection techniques are observation, interviews. The data analysis technique uses Miles and Huberman interactive analysis. The results of this research show that the process of caring for and developing children in daycare has advantages and disadvantages. The important benefits of daycare for children are cognitive development, social development, interpersonal skills. The impact of daycare on parents and children, namely the parents' experience, the emotional impact on children, the advantages and disadvantages of daycare on parents and children.